2019
DOI: 10.3390/jcm8060867
|View full text |Cite|
|
Sign up to set email alerts
|

Sex Differences in the Presence and Severity of Alcohol Hangover Symptoms

Abstract: Studies have demonstrated significant sex differences in alcohol intoxication effects. In contrast, the majority of studies on the alcohol hangover phase did not investigate sex differences. Therefore, the current study examined possible sex differences in the presence and severity of alcohol hangover symptoms. Data from n = 2446 Dutch students (male = 50.7%, female = 49.3%) were analyzed. They reported the presence and severity of 22 hangover symptoms experienced after their past month heaviest drinking occas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 86 publications
(108 reference statements)
6
29
0
Order By: Relevance
“…A similar variability in the presence and severity of hangover symptoms was recently reported by Van Lawick van Pabst et al [18]. Omitting relevant items from a scale can have a significant impact on the overall rating of hangover severity.…”
Section: Presence and Severity Of Hangover Symptomssupporting
confidence: 77%
See 1 more Smart Citation
“…A similar variability in the presence and severity of hangover symptoms was recently reported by Van Lawick van Pabst et al [18]. Omitting relevant items from a scale can have a significant impact on the overall rating of hangover severity.…”
Section: Presence and Severity Of Hangover Symptomssupporting
confidence: 77%
“…Van Schrojenstein Lantman et al [4] also examined the impact of experiencing hangover symptoms on cognitive and physical functioning, and mood in n = 1837 social drinkers who reported A similar variability in the presence and severity of hangover symptoms was recently reported by Van Lawick van Pabst et al [18]. Omitting relevant items from a scale can have a significant impact on the overall rating of hangover severity.…”
Section: Negative Impact Of Hangover Symptomsmentioning
confidence: 82%
“…The study sample was limited to males, as the ethics committee did not approve inducing such an intoxication in females. This is rather unfortunate, as other studies have reported females to experience more severe hangover symptoms than males [24,50], potentially because females tend to metabolite ethanol more slowly than males. In this light, females might experience greater hangover effects, which could translate to more severely impaired behavioral performance.…”
Section: Limitationsmentioning
confidence: 94%
“…Sex differences in alcohol metabolism are well known and may also reflect variability of the presence and severity of hangover symptoms in men and women, and their impact on cognitive and psychomotor functioning and mood [19,20]. Surveys generally indicate higher social consumption levels by males, although gender differences in consequential hangover severity have not been consistently reported, and may be more apparent in women at intermediate BAC levels (0.1-0.3%) [21,22].…”
Section: Introductionmentioning
confidence: 99%